Triptycene-derived thermally activated delayed fluorescence emitters with combined through-bond and through-space charge transfers. (August 2022) - Huang, Yangyang; Zhang, Dong-Hai; Tao, Xiao-Dong; Wei, Zhuangzhuang; Jiang, Shanshan; Meng, Lingyi; Yang, Ming-Xue; Chen, Xu-Lin; Lu, Can-Zhong
Abstract: Thermally activated delayed fluorescence (TADF) materials with through-space charge transfer (TSCT) have recently attracted extensive attention. However, how to rationally design high-performance TSCT-TADF emitters with small ΔEST, high photoluminescence quantum yields (PLQYs) and high stability remains challenging. Herein, two triptycene-derived TADF molecules bearing ortho-donor (D)-acceptor (A) conformations are designed and characterized. These emitters exhibit unique V-shaped face-to-face D-A alignments with significant intramolecular D-A interactions, which mediate TSCT between the D and A moieties in addition to the through-bond charge transfer (TBCT) and facilitate realizing small ΔEST and high efficiencies. Meanwhile, the rigid 3D triptycene scaffold endows the emitters with excellent thermal stability and high film-formation quality. These TADF emitters exhibit small ΔEST of 6.7 and 10.8 meV and high photoluminescence quantum yields of 0.80 and 0.40 in doped films, respectively. The doped OLEDs employing these emitters achieve high external quantum efficiencies up to 20.5%. Graphical abstract: Image 1 Highlights: 3D triptycene scaffold based TADF emitters with photoluminescent efficiency up to 80%. V-shaped face-to-face D-A conformation for constructing through-space charge transfer (TSCT) pathway. High performance OLED with EQE beyond 20%.